Early Outcomes of Isolated Aortic Valve Replacement Through Right Anterior Minithoracotomy Using the Latest-Generation Biological Prosthesis. Issue 1 (January 2021) - Amirjamshidi, Hossein; Vidovich, Courtney; Goodman, Ariana; Knight, Peter A.
Objective: The aim of this study is to evaluate early and intermediate outcomes and hemodynamics of the latest-generation Trifecta valve implanted using right anterior minithoracotomy. Methods: We performed a single-center, retrospective, observational study including 175 individuals who underwent isolated minimally invasive aortic valve replacement with the latest-generation Trifecta valves through a right anterior minithoracotomy between January 2016 and January 2019. Exclusion criteria for follow-up echocardiographic study included concomitant procedures, conversion to median sternotomy, and nonsurvival during the index admission. Analyses addressed implantation safety, 30-day and intermediate-term survival and hemodynamic performance of the valves. Results: Overall, patients were followed with duration ranging from 0.5 to 3 years. Early (<30 days) mortality occurred in 2 patients (1.1%), and there were 9 (5.1%) late (>30 days) deaths. Early thromboembolic events and postoperative bleeding requiring reoperation occurred at a rate of 4.0% ( n = 7) and 6.2% ( n = 11), respectively. Overall in 175 patients who met inclusion criteria for the follow-up echocardiography study, mean gradients across all valve sizes were 41.3 ± 14.9 (standard deviation) mm Hg preoperatively and remained low at 7.2 ± 3.9 mm Hg with mean effective orifice area of 1.8 ± 0.5 cm 2 on the last follow-up echo. There was 1 case of infective prosthetic endocarditis, which did not require valve explant. There were no reoperations due to valve-related problems during the study period. Conclusions: This is the largest series reporting on outcomes of the latest-generation Trifecta valve implanted using right anterior minithoracotomy. Our results demonstrate that this valve can be safely implanted via a minimally invasive approach with excellent early and intermediate outcomes and hemodynamic performance.